Intermedia agenda-setting between mainstream media and blogs : a study of the 2010 Sudanese presidential elections - Abdalla, Saifeldin Hassan Elawad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2014)
This study analyzes intermedia agenda-setting during the 2010 Sudanese presidential elections to determine the intermedia agenda-setting role of socio-political blogs, mainstream news media and citizen journalism. The purpose of this study is to investigate the influence of new media agendas on traditional news media agendas within the theoretical framework of intermedia agenda-setting. Accordingly, this study examines the influence of socio-political blogs on newspaper coverage of the 2010 presidential elections in Sudan at both first and second levels of intermedia agendasetting through content analyses of major national newspapers and socio-political blogs before the Election Day. The study was guided by the following research question: What role do blogs and mainstream media play in intermedia agendasetting? This study applies content analysis, cross-lagged correlation analysis, and Rozelle-Campbell Baseline analysis to explore the causal relationship among newspapers, blogs, and citizen journalism on issues related to the 2010 Sudanese presidential elections. The findings demonstrate proof for intermedia agenda-setting role in Sudanese media across a number of dependent variables. The Sudanese newspapers influenced the agenda of Sudanese blogs; blogs are also gaining a growing influence on the agenda of newspapers. The content analysis found that socio-political blog issue agendas were strongly correlated with the agendas of the newspapers. Results show a lack of intermedia agenda-setting for specific issues examined: the constitution review, economic recovery, the foreign policy, and leadership. The findings also present evidence of intermedia agenda-setting between socio-political blogs and citizen journalism. Results of cross-lagged correlation analyses show that socio-political blogs influenced newspapers at the first level of intermedia agenda-setting. Nonetheless, proof for intermedia agenda-setting did not show up at the second level. Results are discussed in terms of their implications on the field of agenda-setting research as well as limitations and directions for future research.